How to Estimate QT Interval in Patients With Left or Right Bundle Branch Block: A Systematic Review. Issue 3 (May 2021) - Fredholm, Kristian; Højlund, Mikkel; Bjerregaard, Mads Rye; Nielsen, Jens Cosedis; Fink-Jensen, Anders; Correll, Christoph U.
Abstract: Purpose/Background: Prolonged QT interval related to psychopharmacological treatment is a risk factor for potentially life-threatening arrhythmias. Electrocardiographic measurements are recommended in patients with cardiovascular risk factors before initiating treatment with potentially QT-prolonging medications, such as certain antidepressants or antipsychotics. In patients with left bundle branch block (LBBB) or right bundle branch block (RBBB), conventional QT-estimation methods will lead to overestimation of the QT interval, as the conduction defect, reflected by the QRS duration, will increase the QT interval without representing longer repolarization as in drug-induced QT prolongation. Methods/Procedures: We conducted a systematic review of methods to estimate QT interval in the presence of LBBB or RBBB. We searched electronic databases Embase and Medline (last search, August 12, 2020). Findings/Results: We found 8 different methods, including linear correction formulae with and without correction for heart rate, or simpler formula correcting QRS duration with empirically derived modifiers. Only 3 of 8 methods were applicable in the presence of RBBB, whereas all 8 methods could be applied in the presence of LBBB. Implications/Conclusions: The QT interval is overestimated in patients with LBBB or RBBB, when using conventional measurements. Several alternative correction formulae exist, which can be applied using standard measurements from ordinary electrocardiographic readings. However, it is currently unknown whether or not the QT prolongation observed in the presence of bundle branch block significantly increases the risk of arrhythmias, as these formulae have not been tested against patient-specific clinical outcomes.